Plectotropis yonganensis sp. nov. (Gastropoda: Bradybaenidae) from China, with revision of two Chinese camaenid species (Gastropoda: Camaenidae) - Zhou, Wei-Chuan; Xiao, Qiong; Chen, De-Niu; Hwang, Chung-Chi (Zootaxa, 2011)
The terrestrial snail genus Ganesella Blanford, 1863, sensu lacto by Zilch (1959–1960), is mainly distributed in the Oriental region from Japan, through south of the Yangtze of China to South-east and South Asia. Most of these land snails are endemic species with narrow geographic distribution (Tryon 1888; Pilsbry 1894; Zilch 1959–1960, 1966; Richardson 1985, Chen & Gao 1987; Azuma 1995). The genus is characterized in having thin, smooth or weakly ridged shell, slightly descent body whorl in front, toothless aperture, expanded to reflected lips, long and narrow foot, long penis with a caecum (= penial appendix) and a flagellum. However, the anatomical characters of the type species, G. capitium Benson, 1848, are still wanting. A major part of its members have been assigned to different genus according to shell characters. The species in East-Asia, i.e., Japan, Korea and Taiwan, were assigned to the genus Satsuma (+ syn. Coniglobus Pilsbry & Hirase, 1906 and Luchuhadra Kuroda & Habe, 1949). About 100 species are still catalogued in Ganesella (Richardson 1985).